2021
DOI: 10.3389/fncel.2021.780447
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hydrogen Sulfide Donor Reduces Pilocarpine-Induced Status Epilepticus and Regulates Microglial Inflammatory Profile

Abstract: Although epilepsy is one of the most common neurologic disorders, there is still a lack of effective therapeutic drugs for it. Recently, we synthesized a novel hydrogen sulfide (H2S) donor, which is found to reduce seizures in animal models effectively. But it remains to be determined for its mechanism. In the present study, we found that the novel H2S donor could reduce pilocarpine-induced seizures in mice. It alleviated the epileptic behavior, the hippocampal electroencephalography (EEG) activity of seizures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…37 The appearance of the relationship with similar direction and strength between H 2 S and arginase activity in the group of chronic alcoholic hepatitis is also related to the biological effects of alcohol, namely its ability to decrease arginase activity, while H 2 S can increase its activity. [38][39] The inversely proportional strong relationship between the concentrations of H 2 S and L-oxyproline under conditions of chronic alcoholic hepatitis can be explained by the origin of free L-oxyproline, which under conditions of excessive accumulation of alcohol is released from collagen fibers during oxidative stress, while H 2 S is a powerful antioxidant. 40 Stimulation of the activation of the AMPK cascade in the background of simulation of alcohol intoxication significantly enhances the effect of H 2 S on the nitric oxide system.…”
Section: Discussionmentioning
confidence: 99%
“…37 The appearance of the relationship with similar direction and strength between H 2 S and arginase activity in the group of chronic alcoholic hepatitis is also related to the biological effects of alcohol, namely its ability to decrease arginase activity, while H 2 S can increase its activity. [38][39] The inversely proportional strong relationship between the concentrations of H 2 S and L-oxyproline under conditions of chronic alcoholic hepatitis can be explained by the origin of free L-oxyproline, which under conditions of excessive accumulation of alcohol is released from collagen fibers during oxidative stress, while H 2 S is a powerful antioxidant. 40 Stimulation of the activation of the AMPK cascade in the background of simulation of alcohol intoxication significantly enhances the effect of H 2 S on the nitric oxide system.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that SE + H 2 S group had a shorter duration of seizure compared to the SE group. Additionally, this group showed delayed onset of seizure, reduced damage to the hippocampus and reduced pro-inflammatory state in microglia compared to the SE control group [ 62 ].…”
Section: Cns-related Disorders and H 2 Smentioning
confidence: 99%